Quantitative Lung Index, Contralateral Lung Area, or Lung‐to‐Head Ratio to Predict the Neonatal Outcome in Isolated Congenital Diaphragmatic Hernia?. (1st March 2013) - Ruano, Rodrigo; Takashi, Eduardo; Silva, Marcos Marques da; Haeri, Sina; Tannuri, Uenis; Zugaib, Marcelo
Abstract : Objectives: To estimate the accuracy of the quantitative lung index and contralateral lung area for prediction of the neonatal outcome in isolated congenital diaphragmatic hernia in comparison to other available prediction models. Methods: Between January 2004 and December 2010, 108 fetuses with isolated (82 left‐sided and 26 right‐sided) congenital diaphragmatic hernia were prospectively evaluated. The quantitative lung index and observed‐to‐expected contralateral lung area were measured and compared to the neonatal survival rate and severe postnatal pulmonary arterial hypertension, along with the lung‐to‐head ratio, observed‐to‐expected lung‐to‐head ratio, and observed‐to‐expected total lung volume. Results: Overall neonatal mortality was 64.8% (70 of 108). Severe pulmonary arterial hypertension was diagnosed in 68 (63.0%) of the cases, which was associated with neonatal death ( P < .001). Both the quantitative lung index and observed‐to‐expected contralateral lung area were significantly associated with neonatal survival and pulmonary arterial hypertension ( P < .001), with accuracy to predict survival of 70.9% and 70.0%, respectively, and accuracy to predict hypertension of 78.7% and 72.0%; however, they were both less accurate than the observed‐to‐expected total lung volume (83.3% and 86.1%; P < .01). The lung‐to‐head ratio (73.1% and 78.7%) and observed‐to‐expected lung‐to‐head ratio (75.9% and 72.2%; P > .05) had similar accuracy as the quantitative lung index and observed‐to‐expected contralateral lung area. Conclusions: The observed‐to‐expected total lung volume is the most accurate predictor of the neonatal outcome in cases of isolated congenital diaphragmatic hernia. Both the quantitative lung index and observed‐to‐expected contralateral lung area, albeit reasonably accurate, do not produce the same level of accuracy and render similar results as the lung‐to‐head ratio and observed‐to‐expected lung‐to‐head ratio.